L-Theanine Improves the Gelation of Ginkgo Seed Proteins at Different pH Levels - Luyan Zhang; Huifang Ge; Jing Zhao; Changqi Liu; Yaosong Wang (Gels, 2024)
L-theanine (L-Th), a non-protein amino acid naturally found in teas and certain plant leaves, has garnered considerable attention due to its health benefits and potential to modify proteins such as ginkgo seed proteins, which have poor gelling properties, thereby expanding their applications in the food industry. The objective of this study was to investigate the impact of varying concentrations of L-Th (0.0%, 0.5%, 1.0%, and 2.0%) on the gelling properties of ginkgo seed protein isolate (GSPI) at various pH levels (5.0, 6.0, and 7.0). The GSPI gels exhibited the highest strength at a pH of 5.0 (132.1 ± 5.6 g), followed by a pH of 6.0 (95.9 ± 3.9 g), while a weak gel was formed at a pH of 7.0 (29.5 ± 0.2 g). The incorporation of L-Th increased the hardness (58.5–231.6%) and springiness (3.0–9.5%) of the GSPI gels at a pH of 7.0 in a concentration-dependent manner. However, L-Th did not enhance the gel strength or water holding capacity at a pH of 5.0. The rheological characteristics of the GSPI sols were found to be closely related to the textural properties of L-Th-incorporated gels. To understand the underlying mechanism of L-Th’s effects, the physicochemical properties of the sols were analyzed. Specifically, L-Th promoted GSPI solubilization (up to 7.3%), reduced their hydrophobicity (up to 16.2%), reduced the particle size (up to 40.9%), and increased the ζ potential (up to 21%) of the sols. Overall, our findings suggest that L-Th holds promise as a functional ingredient for improving gel products.